General surgical injuries in survivors of the M1 Kegworth air crash. Nottingham, Leicester, Derby, Belfast Study Group. - Rowles, J. M. (Royal College of Surgeons of England, 1990)
The general surgical consequences of the M1 Kegworth air crash are described. Considering the severe nature of the injuries sustained by the survivors, surprisingly few required general surgical intervention. Intra-abdominal injuries were rare despite the abdomen's apparent vulnerability to injury; only five laparotomies were performed. However, 30 (34%) of survivors demonstrated significant bruising from lap belts and 13 patients had haematuria. The majority of operations carried out were orthopaedic related.